Construction and Characterization of Virus-Like Particles: A Review - Zeltins, Andris (Molecular biotechnology, 2013)
Over the last three decades, virus-like particles (VLPs) have evolved to become a widely accepted technology, especially in the field of vaccinology. In fact, some VLP-based vaccines are currently used as commercial medical products, and other VLP-based products are at different stages of clinical study. Several remarkable advantages have been achieved in the development of VLPs as gene therapy tools and new nanomaterials. The analysis of published data reveals that at least 110 VLPs have been constructed from viruses belonging to 35 different families. This review therefore discusses the main principles in the cloning of viral structural genes, the relevant host systems and the purification procedures that have been developed. In addition, the methods that are used to characterize the structural integrity, stability, and components, including the encapsidated nucleic acids, of newly synthesized VLPs are analyzed. Moreover, some of the modifications that are required to construct VLP-based carriers of viral origin with defined properties are discussed, and examples are provided.